Theoretical analysis of sewing needle heating and cooling - Mazari Adnan; Novosad Jan (Journal of Engineered Fibers and Fabrics)
There is a lot of research done in the field of heating of sewing needle at high-speed sewing, most of these theoretical models only calculate the gain of heat and neglect the heat losses by convection. In this research the total heat balance will be theoretically analysed considering the heat gain by needle by friction of thread and fabric to the needle at high speed, whereas the maximum hot loss is considered by conduction, convection and radiation. In which two different approach of parallel flow and cross flow around the hot needle is considered to predict more precise sewing needle temperature. The results are further compared with other theoretical models and experimental results. This is the one of the few models in which the heat of convection is considered as the cooling of sewing of needle.